Cardiac Mechanics in Isolated Bicuspid Aortic Valve Disease With Normal Ejection Fraction: A Study of Various Valvular Lesion Types. Issue 47 (November 2015) - Zhang, Xijun; Zhu, Meihua; He, Tao; Yuan, Jianjun; Zhu, Haohui; Morrisroe, Dennis E.; Ashraf, Muhammad; Sahn, David J.
Abstract : Abstract: Aortic stenosis (AS) and aortic regurgitation (AR) are associated with congenital isolated bicuspid aortic valve (BAV) disease. The chronic pressure overload of AS and the volume overload of AR are known to impair the left ventricular function. This study assessed whether two-dimensional speckle tracking echocardiography (2D-STE) is capable of detecting the myocardial dysfunction associated with BAV caused by various aortic valve lesions in patients retaining normal ejection fraction (EF). Thirty-two isolated BAV patients and 20 healthy tricuspid aortic valve (TAV) volunteers were recruited. BAV patients were divided into 4 subgroups based on aortic valvular lesion types: normal function (NF) group, isolated AS group, isolated AR group, and a group who had both AS&AR. Myocardial strain and degree of twist were analyzed and compared between the BAV and TAV groups, as well as between valvular lesion groups and the NF group. Compared with healthy TAV controls, global radial strain (GRS), global circumferential strain (GCS), global longitudinal strain (GLS), and twist angle absolute values were lower in the BAV group ( P  < 0.05). The AS, AR, and AS&AR groups all demonstrated a significant decrease in GRS and GCS when compared with the TAV group. The AS and AS&AR groups demonstrated lower GLS than the TAV group, and the smallest degree of twist was detected in the AR group. There were no significant differences between the NF and TAV groups. The AR and AS&AR groups demonstrated significant differences in multiple parameters of cardiac mechanics compared with the NF group. 2D-STE is able to detect altered cardiac mechanics associated with aortic lesion types in BAV patients with normal EF compared with normal TAV controls, and so can provide valuable information for clinical decision-making.